UNRAVELING GKI YASMINâS CASE: PRELIMINARY RESEARCH - Ruhana, Akmal Salim (LIPI-Press, 2013)
The case of GKI Yasmin in Bogor, West Java, has been a national or, furthermore, a global issue on interreligious relation. It has also tested some regulations on building a house of worshipâincludes PBM No. 9 and 8 of 2006. This paper elaborates some facts on this case from the wide perspectives: regulation and non-regulation aspects (politics, economics, social, culture, and religious). The purpose of the research is to know causes of the conflict and some factors supported and unsupported to the solution. Enriched by some interviews with some key-informan, this research is written based on descriptive-analytic method. The research shows some causes of conflict: the debate on the âillegalâ IMB (building permit), the bias of information, and a kind of pseudo-intolerance.